IN VITRO SENSITIVITY PROFILES OF ENTERIC BACTERIA ASSOCIATED WITH DIARRHEIC PATIENTS WITHIN KATSINA METROPOLIS, KATSINA STATE, NIGERIA : - Odewade, Joseph; Fasogbon, Albert; Onyekachi, Felix (FUDMA Journal of Sciences, 2020)
Diarrheal disease is a leading cause of mortality and morbidity across the globe. However, there is little information on the prevalence and antimicrobial sensitivity patterns of microbes associated with diarrheic patients within Katsina Metropolis, Nigeria, hence, the need for this study. Forty (40) stool samples were collected from Federal Medical Center, Katsina, Katsina State, Nigeria. Isolation and identification of the bacteria from the stool samples were carried out using standard microbiological techniques. Antibiotics sensitivity testing was carried out on all the bacterial isolates using disk diffusion method. Seventeen (17) bacterial isolates were isolated from three different genera. These include: Escherichia coli (58.82%), Salmonella typhi (29.41%) and Shigella dysenteriae (11.77%). The results of antibiotics sensitivity test showed a high (100%) resistance to amoxicillin, 70.59% resistance to streptomycin, 41.18% resistance to nalixidic acid and least (17.65%) resistance to imipenem. Multi drug resistant Escherichia coli and Shigella species were also detected. The high level of antibiotic resistance among bacterial isolates obtained from stool samples of diarrheic patients is quite alarming and requires urgent public health attention. Hence, further studies are required for the molecular detection of the resistant genes in these bacteria.